Investigating the qualitative components of meaning and the role of the endowment tradition in Iranian urban spaces - Norouzian, Mohammad Mehdi (Edelweiss Applied Science and Technology, 2024)
The endowment phenomenon, as one of the forces of the city of Afrin and the shaper of Iranian-Islamic cities, has had a great impact on the shaping of human-made environments and the organization of the physical spaces of cities. In addition to influencing the physical development of the city, the Dedicated lands have also been affected by it, because during the physical development of the city, they have changed from their original state (barren, agriculture, gardens, etc.) and turned into an urban fabric. Based on the descriptive-analytical method, this article tries to investigate how this religious factor is shaped in the Iranian-Islamic city and how the change and transformation of Dedicated lands and its role in the development or non-development of Isfahan city. Finally, relying on the recognition of the effect of this factor on the qualitative components of meaning, such as neighborhood identity and the sense of security of the environment, in Sheikh-Sadoogh and Mehr-Abad neighborhoods, which are respectively old and new neighborhoods of Isfahan city. Describe and analyze data collection through a questionnaire using SPSS software. The results of the research indicate that the presence of endowment as an important factor in the appearance of Islamic cities has a profound effect on the components of meaning, such as neighborhood identity and the sense of security of the environment, in addition to the physical structure of the city. In this regard, neighborhoods with more endowments have a significant relationship with neighborhood identity and a sense of security in the neighborhood, compared to neighborhoods with fewer endowments.